4(x+3)+2=2(x-3)

Simple and best practice solution for 4(x+3)+2=2(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x+3)+2=2(x-3) equation:


Simplifying
4(x + 3) + 2 = 2(x + -3)

Reorder the terms:
4(3 + x) + 2 = 2(x + -3)
(3 * 4 + x * 4) + 2 = 2(x + -3)
(12 + 4x) + 2 = 2(x + -3)

Reorder the terms:
12 + 2 + 4x = 2(x + -3)

Combine like terms: 12 + 2 = 14
14 + 4x = 2(x + -3)

Reorder the terms:
14 + 4x = 2(-3 + x)
14 + 4x = (-3 * 2 + x * 2)
14 + 4x = (-6 + 2x)

Solving
14 + 4x = -6 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
14 + 4x + -2x = -6 + 2x + -2x

Combine like terms: 4x + -2x = 2x
14 + 2x = -6 + 2x + -2x

Combine like terms: 2x + -2x = 0
14 + 2x = -6 + 0
14 + 2x = -6

Add '-14' to each side of the equation.
14 + -14 + 2x = -6 + -14

Combine like terms: 14 + -14 = 0
0 + 2x = -6 + -14
2x = -6 + -14

Combine like terms: -6 + -14 = -20
2x = -20

Divide each side by '2'.
x = -10

Simplifying
x = -10

See similar equations:

| (4x^5+3y)dx-xdy=0 | | -100=4k-8(2+2k) | | 3x+2=1+2x | | 2x-3=37-3x | | .5(x)4=48 | | r-6-26=13 | | sqrt(25)=x | | -2p-3(4-3p)=4(p-3)-12 | | 2x+11y=19 | | x(x)-6=13 | | 4y(3y+3)=118 | | 4x^4+2x^2-6=0 | | 3x-2x^2-4=0 | | -19=11-6X | | (4x-2)4x-2+5x(5x)= | | -5y-7(9y+7)=1+3(-7-y) | | y-9(5)=3 | | 4x^2+0.2x+0.01=0 | | 4(u+1)-7=3(u-1)+7 | | -x+3.9forx=-7.2 | | (4x+2)=-34 | | 9+4(-4)+3=-4 | | (4x+2)=34 | | 0.80x+0.20(60)=0.40(78) | | -3.6-7.2=12.7-6.1b | | (4x-2)(4x-2)+(5x)(5x)= | | 10x-4-6x=5x-7 | | (-10)+4=-2(-10)+-6 | | 2a+8=4a+16 | | 5(4x-4)-9=-31 | | 216=8(-5r-3) | | (3x+y*1)=(7*2x-3y) |

Equations solver categories